Effective Corporate Codes of Ethics: Perceptions of Code Users - Schwartz, Mark S. (2004)
The study examines employee, managerial, and ethics officer perceptions regarding their companies’ codes of ethics. The study moves beyond examining the mere existence of a code of ethics to consider the role that code content and code process (i.e. creation, implementation, and administration) might play with respect to the effectiveness of codes in influencing behavior. Fifty-seven in-depth, semi-structured interviews of employees, managers, and ethics officers were conducted at four large Canadian companies. The factors viewed by respondents to be important with respect to code effectiveness include: provisions of examples; readability; tone; relevance; realism; senior management support; training; reinforcement; living up to standards; reporting requirement; anonymous phone line; communicating violations; and enforcement. The factors found to be potentially important include: justification for provisions; employee involvement; and sign-off requirements. Factors found not to be important include: objectives for the code; prior distribution; testing; and relating one’s performance review to compliance with the code.
Keywords: Process; Ethics; Effectiveness; Content; Codes; Behavior